Optimalisasi Pengelolaan Aset Tetap oleh BPKAD Kabupaten Jember - Pamungkas, Tree Setiawan; Helpiastuti, Selfi Budi; Nurqarin, Alfrida Septya (Department of Public Administration, Parahyangan Catholic University, 2024)
Regional assets management is a critical component of financial management. Jember county's financial management and regional assets are in charge of financial management, in accordance with Peraturan Bupati Nomor 8 Tahun 2023. According to the performance report of the BPKAD government district jember 2023, annual performance gains on target asset percentage remains with legal documentation by 2023 went down and almost reached the target. Although there has been a decline, the attainment has been highly satisfactory. The goal of this study is to describe the performance of BPKAD assets in the management of jember's permanent assets. The study uses the